Elective Transjugular Intrahepatic Portosystemic Shunt Using Viatorr Stent-Grafts: A Single-Center Experience from China. Issue 1 (29th June 2022) - Li, Yu-Hua; Wan, Yue-Meng; Wu, Hua-Mei; Huang, Song-Quan
Background and Aims: Transjugular intrahepatic portosystemic shunt (TIPS) is a well-established approach for the management of variceal bleeding, refractory ascites, hepatic hydrothorax, and preoperative treatment of portal hypertension prior to major abdominal surgery in patients with compensated cirrhosis, and so on. This study aimed to investigate the safety and long-term efficacy of TIPS implantation using Viatorr TIPS stent-grafts. Material and Methods: A cohort of 59 patients undergoing TIPS placement using Viatorr TIPS stent-grafts were included, and the periprocedural events, and long-term mortality, shunt dysfunction, variceal rebleeding and incidence of hepatic encephalopathy (HE) were analyzed. Results: The technical success rate was 100%. The median portosystemic pressure gradient was reduced from 21 mmHg (interquatile range: 19–25) to 13 mmHg (interquatile range: 10–16) before and after TIPS, leading to a hemodynamic success rate of 72.9%. The cumulative rate of overall mortality was 34.2% at five years, and direct bilirubin (hazard ratio [HR] = 1.336, 95% confidence interval [CI]: 1.050–1.700, P = 0.018) and post-TIPS right atrial pressure (HR = 1.238, 95% CI: 1.015–1.510, P = 0.035) were independent predictors for mortality. The cumulative rates of shunt dysfunction and variceal rebleeding were 11.0% and 28.3% at five years, respectively, and portal venous pressure gradient (HR = 2.572, 95% CI: 1.094–6.047, P = 0.030) was the only independent predictor for shunt dysfunction. The cumulative four-year HE-free rate was 48.6%. No severe adverse event was noted during TIPS procedures. Conclusion: Elective TIPS implantation using Viatorr TIPS stent-grafts is generally safe, and the long-term efficacy is favorable for the treatment of cirrhotic patients with recurrent variceal bleeding or refractory ascites.